+0  
 
0
59
1
avatar

If f(x)=5x-12, find a value for x so that f^-1(x)=f(x+1).

 May 11, 2020
 #1
avatar+21935 
0

If  f(x)  =  5x -12

then  f(x + 1)  =  5(x + 1) - 12  =  5x + 5 - 12  =  5x - 7

 

Now, let's find the inverse of  f(x).

Let                                         y  =  f(x)

then                                       y  =  5x - 12

interchange  x  and  y:           x  =  5y - 12

solve for y:                     x + 12  =  5y

                                (x + 12) / 5  =  y

 

So:  f-1(x)  =  (x + 12 ) / 5

 

Set  f-1(x)  =  f(x + 1):         (x + 12) / 5  =  5x - 7

multiply by 5:                             x + 12  =  25x - 35

solve:                                               47  =  24x

                                                          x  =  47/24

 May 11, 2020

21 Online Users

avatar
avatar
avatar
avatar
avatar